Una revisión de los estimadores óptimos de calibración usando métodos de cuasi-verosimilitud en muestreo bifásico (2009)
Optimal calibration estimators use auxiliary information to produce more eﬃcient estimates. When the auxiliary information is not available, we proceed to design a two-phase sampling where the auxiliary information is gather in the ﬁrst phase and it is used in the design or estimation of the second phase. We compare the eﬃciency of the optimal calibration estimators when the relationship between the variable of interest and the auxiliary information is both linear and log-linear. In this last escenario, we make use of the quasi-likelihood method in order to estimate the super-population parameters.